Self-efficacy among Nursing Students in Online Learning: A Cross-sectional Study in Banten - Hohi Hoschinthya Lobo Djingi; Indah Pratiwi Pomali; Vamy Pellondou; Riama Marlyn Sihombing; Komilie Situmorang (CV. Inara, 2026)
An increasingly important part of nursing education is online learning. Students' self-efficacy, or their confidence in their capacity to complete academic assignments, is a key factor in determining their level of engagement, performance, and flexibility in digital settings. Recent research suggests that among nursing students, self-efficacy is positively correlated with academic achievement, learning engagement, and preparedness for e-learning. The study aimed to characterize the degree of self-efficacy among online learning nursing students. This study applied a cross-sectional, descriptive design with 295 undergraduate nursing students at one private university in West Indonesia. The method employed was total sampling. A 14-item Likert-type questionnaire based on Bandura's dimensions (level, strength, and generality) was used to gauge self-efficacy. The instrument demonstrated good internal consistency (Cronbach's α = 0.944) following verification in a pilot test. Google Forms was used to gather data online between February and March of 2021. The findings revealed 23.7% of students demonstrated high self‑efficacy, whereas 53.2% of students have moderate self-efficacy and 23.1% of respondents found low self-efficacy. Nursing students who have high self-efficacy expressed more confidence in their ability to manage online tasks, finish projects, and handle technical challenges. These results are consistent with new research showing that technology readiness, online learning satisfaction, device accessibility, and structured pedagogical approaches all boost online learning self-efficacy. In general, nursing students showed moderate levels of self-efficacy when learning online. Learning outcomes can be maximized by enhancing self-efficacy through improved learning design, increased technical assistance, and readiness-building initiatives.